Deciphering the Environmental Code: SEM-EDX Analysis of Lead and Mercury Distribution in Enhalus Acoroides From Kayeli Bay, Indonesia - Natsir, Nur Alim; AF, Asyik Nur Allifah; T, Rosmawati; ., Surati; Jamdin, Zamrin (Journal of Ecohumanism, 2024)
Background: Illegal gold mining activities around Kayeli Bay have led to increased heavy metal contamination that has the potential to impair water quality and growth of Enhalus acoroides, an important seaweed species. This study aimed to investigate the distribution and concentration of heavy metals Pb and Hg in Enhalus acoroides organs (roots, rhizomes, and leaves) using SEM-EDX techniques and evaluate the impact of mining activities on the surface microstructure of these organs. Methods: Enhalus acoroides samples were collected from ten sampling points in Kayeli Bay, which were selected based on potential heavy metal contamination. SEM-EDX analysis was performed to assess the surface microstructure and distribution of heavy metals in the seaweed samples. Results: Results showed significant differences in Pb and Hg concentrations among samples from different locations, with Hg content consistently higher than Pb. Surface microstructure analysis showed morphological changes in roots, rhizomes, and leaves exposed to heavy metals, indicating environmental stress in Enhalus acoroides. Conclusion: This study confirmed the negative impact of heavy metal contamination on Enhalus acoroides in Kayeli Bay due to illegal gold mining activities. High concentrations of heavy metals, especially Hg, in seaweed organs indicate potential risks to marine ecosystem health and the sustainability of fisheries resources. These findings emphasize the need for stricter environmental monitoring and management to protect this important marine habitat from heavy metal pollution.